2008
DOI: 10.1007/s00702-008-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

MKC-231, a choline uptake enhancer: (3) mode of action of MKC-231 in the enhancement of high-affinity choline uptake

Abstract: MKC-231, a putative cholinergic activity, is reported to improve learning and memory impaired in AF64A-treated animals. MKC-231 enhances high-affinity choline uptake (HACU) known as the rate-limiting step of acetylcholine (ACh) synthesis. We investigated the mode of action (MOA) of HACU enhancement by MKC-231. Intracerebroventricular (i.c.v.) injections of AF64A (3 nmol/brain) resulted in significant HACU reduction in hippocampal synaptosomes. Treatment with MKC-231 increased Vmax of HACU and Bmax of [3H]-HC-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…33 Animal experiments have reported that MKC-231 significantly improves the learning and memory deficits associated with cholinergic hypofunction by affecting the trafficking of CHT1 and increasing the number of transporters working for HACU at the synaptic membrane. [33][34][35] Furthermore, MKC-231 could antagonize phencyclidine-induced behavioural deficits through increases in septal cholinergic neurons. 36 According to our data, MKC-231 also enhances the normal colonic motility of control rats through upregulation of CHT1 and elevated ACh production.…”
Section: Discussionmentioning
confidence: 99%
“…33 Animal experiments have reported that MKC-231 significantly improves the learning and memory deficits associated with cholinergic hypofunction by affecting the trafficking of CHT1 and increasing the number of transporters working for HACU at the synaptic membrane. [33][34][35] Furthermore, MKC-231 could antagonize phencyclidine-induced behavioural deficits through increases in septal cholinergic neurons. 36 According to our data, MKC-231 also enhances the normal colonic motility of control rats through upregulation of CHT1 and elevated ACh production.…”
Section: Discussionmentioning
confidence: 99%
“…MKC-231, known as a choline uptake enhancer, has been reported to take CHT1 as its principal target. 40 , 41 Animal experiments have demonstrated that oral administration of MKC-231 significantly improved the learning and memory deficit associated with cholinergic hypofunction by directly affecting the trafficking of CHT1 and increasing the number of transporters. 40 , 41 Furthermore, MKC-231 could antagonize phencyclidine-induced behavioral deficits and reduction in septal cholinergic neurons in rats.…”
Section: Discussionmentioning
confidence: 99%
“…40 , 41 Animal experiments have demonstrated that oral administration of MKC-231 significantly improved the learning and memory deficit associated with cholinergic hypofunction by directly affecting the trafficking of CHT1 and increasing the number of transporters. 40 , 41 Furthermore, MKC-231 could antagonize phencyclidine-induced behavioral deficits and reduction in septal cholinergic neurons in rats. 42 These reports suggest that MKC-231 could be a therapeutic drug for the treatment of Alzheimer’s disease and schizophrenia, but without any significant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The Cresset field based virtual screening tool, Blaze (formerly called FieldScreen), (Cheeseright et al, 2008 , 2009 ) was utilized to search the full Pfizer compound screening collection to identify compounds similar to literature CHT positive allosteric modulator (PAM) MKC-351/coluracetam (Takashina et al, 2008a , b ) or CHT negative allosteric modulator (NAM) ML-352 (Ennis et al, 2015 ). Similarity was assessed using 50% 3D electrostatic and hydrophobic properties (Cheeseright et al, 2006 ) and 50% shape (Grant et al, 1996 ).…”
Section: Methodsmentioning
confidence: 99%
“…There is comparative paucity of relevant known tool molecules that modulate CHT function: published orthosteric inhibitors include hemicholinium-3 (HC-3) and related analogs which have been broadly used since their first discovery in 1955 (Ferguson and Blakely, 2004 ). In addition there is the recently described negative allosteric modulator (NAM) ML-352 (Ennis et al, 2015 ) and putative positive modulators of transporter function including MKC-231/coluracetam (Bessho et al, 2008 ; Takashina et al, 2008a , b ) and staurosporine (STS) (Ruggiero et al, 2012 ). ML-352 and MKC-231 were used as seeds for generating the first set of 887 compounds via Cresset software (a computational approach that generates a 3-dimensional electrostatic shape or “field” which illustrates how the compound may interact with the target).…”
Section: Introductionmentioning
confidence: 99%